Effectiveness of Cognitive Behavioral Hypnotherapy to Reduce Smoking in Anxiety-Prone Individuals (Medical Forum Monthly, 2024)
Objective: to assess the efficacy of Cognitive Behavioral and Hypnotic interventions in reduction of smoking in anxious prone adults.Study Design: Observational studyPlace and Duration of Study: This study was conducted at the Professional environment at Institute of Professional Psychology, Bahria University Karachi Campus (BUKC) from January 2023 to September 2023.Methods: The study recruited 37 male smokers aged 19 to 24 from the University of Karachi, chosen based on their frequent experience of anxiety leading to smoking as a coping mechanism. Cognitive Behavioral Hypnotherapy (CBHT) was administered over eight sessions, each lasting 45 minutes to 1 hour, focusing on reducing smoking and anxiety levels. Pre- and post-intervention anxiety levels were assessed using the Beck Anxiety Inventory (BAI). Statistical analysis, including paired sample t-tests, was conducted using SPSS version 23 with a significance level set at p < 0.05.Results: The intervention led to a significant reduction in smoking habits among participants, with the average number of cigarettes smoked per day decreasing from 15.2 to 8.32. Additionally, there was a substantial decrease in anxiety levels, with participants experiencing an average reduction of 9 points in anxiety scores.Conclusion: Cognitive Behavioral Hypnotherapy intervention can be helpful as short term therapy intervention and effective for both anxiety symptoms and reduction of smoking.